The prevalence of cryptosporidium and giardia infecting long-tailed macaques and proboscis monkeys in The Lower Kinabatangan Wildlife Sanctuary - Surdensteeve Peter (2020)
The current study was aimed in determining the occurrence of these parasitic protozoans in two large populations of nonhuman primates in the Lower Kinabatangan Wildlife Sanctuary (LKWS), the long- tailed macaques and proboscis monkeys. The objectives of the study were to 1) determine the prevalence of Cryptosporidium and Giardia infection in long-tailed macaques and proboscis monkeys and 2) To determine the factors that were influencing the prevalence of Cryptosporidium and Giardia that were infecting both long-tailed macaques and proboscis monkeys in the LKWS. Fecal samples were collected noninvasively and the infection of both parasites was detected by using immunochromatographic test strips (CoproStrip ™, Savyon Diagnostics, Ltd, Israel). PCR was used to clearly distinguish the donor of the samples since both primate species were always found close to one another. From the analysis, 44.71 % (N=38) of tested samples were positive for Cryptosporidium spp. and only 17.64% (N=14) of samples were positive for Giardia spp. The result also showed a contrasting pattern in each host-parasite association, with Giardia spp. achieving higher but still moderate prevalence in long-tailed macaques (33.33%) and Cryptosporidium spp. achieving unexpectedly high prevalence in proboscis monkeys (87.5%). Among the six variables (host species, habitat types, average weekly rainfall, host abundance, primate diversity and river sections) host species was the most important factor that influences the prevalence of Cryptosporidium and Giardia infection. However, due to the limitation of the current study, I am not able to differentiate whether the current finding were due to (i) the two nonhuman primate species encounter each parasite at very different rates in the environment; (ii) each species has different resistance traits for each parasite; (iii) there is interspecies competition between parasites, where one parasite species inhibit ( directly or indirectly) the establishment of other parasites in its host; or (iv) some other unknown reason. However, the current study did managed to achieve its aim and is successful in documenting the occurrence of Cryptosporidium and Giardia in nonhuman primates, and is the first to report in Sabah. For future studies, researchers need to focus on the zoonotic potential of these parasites.